A Retrospective Case Series of High-Frequency Spinal Cord Stimulation (HF10-SCS) in Neurogenic Bladder Incontinence. Issue 1 (30th August 2018) - Schieferdecker, Simon; Neudorfer, Clemens; El Majdoub, Faycal; Maarouf, Mohammad
Abstract: BACKGROUND: Current treatment options for bladder disorders of neurogenic etiology often leave unsatisfactory results. Therefore, new and effective treatments must be investigated. High-frequency spinal cord stimulation (HF-SCS) at 10 kHz has proven to be effective in the treatment of refractory chronic back and leg pain. OBJECTIVE: To evaluate the efficacy of HF-SCS at 10 kHz in alleviating lower urinary tract dysfunction and bladder incontinence in 5 patients with underlying neurological disease or spinal cord injury, through retrospective study. METHODS: Urodynamic parameters such as voiding frequency, residual volume, episodes of incontinence, and the patients' subjective impression impairment of life were assessed and compared pre- and postoperatively. Reduction in pain intensity was assessed as change on the Numeric Rating Scale (NRS). RESULTS: All 5 patients had significantly positive outcomes. Episodes of leakage per day improved by 83% on average. Quality of life questionnaires and subjective bother scale revealed an improvement of 36% and 57%, respectively. Individual symptoms among the patient group such as residual volume also responded to the treatment as well. Mean pain NRS of 8.6 cm was reduced to 3.9 cm (55%) at 6 mo follow-up. CONCLUSION: HF-SCS at 10 kHz significantly alleviated symptoms of neurogenic bladder incontinence in patients suffering from neurological disease or spinal cord injury. However, larger and prospective, randomized studies are necessary to make a clear statement regarding the efficacy of this therapy in lower urinary tract dysfunction and bladder incontinence.